Actividades lúdicas dirigidas al fortalecimiento de la convivencia escolar del subnivel 2 de la Unidad Educativa Francisco Robles - Litardo Cerezo, Denisse Liseth (2023)
This research work tries to show how important playful activities are for the development of a good school coexistence in each of the educational institutions, because they allow to create in children a sense of communication and interaction with the environment that surrounds them. That is why, in the Educational Unit "Francisco Robles" located in the Babahoyo canton, it was evident that certain children in sublevel 2, do not have an adequate coexistence among students, making this factor intervene in their teaching-learning process. For this reason, the implementation of ludic activities that contribute to the creation of interactive environments, in which the child will learn to work together with others, is required. Within this research, descriptive, field, documentary and exploratory research are used, since they are the most used types of research at the time of investigating a problem. In addition, there is the presence of the mixed research approach, the non-experimental research design and the inductive and deductive method. As a result of this research carried out with the children of sublevel 2, it was possible to verify the lack of group coexistence in the classroom, thus generating a problem of trust in others. That is why it is necessary to implement playful activities that are precursors of school coexistence, which allows each of the children to communicate and coexist with others in a pleasant way.